2022
DOI: 10.1108/ccsm-03-2021-0041
|View full text |Cite
|
Sign up to set email alerts
|

Early evidence of leadership skills and strategies in managing the impact of COVID-19 pandemic in the hospitality industry

Abstract: PurposeGiven the critical consequences of the current Coronavirus (COVID-19) crisis worldwide, displaying good leadership has been of utmost importance. Hospitality has been among the industries that have been hit the hardest by the pandemic, and it requires exceptional leadership skills unique to this crisis and sector. This multi-country study aims to contribute to the understanding of some of the most important skills and strategies that leaders in the hospitality industry may use to navigate the COVID-19 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…In the extant literature, many attempts have been made to search for novel strategies that help T&H firms overcome such harsh and turbulent situations. Various recent studies have also pointed to the role of leader in supporting T&H firms to achieve better outcomes during COVID-19 pandemic (Nazarian et al, 2022;Ho et al, 2022;Hahang et al, 2022). For example, Talu and Nazarov (2020) found that leaders relied on their competences such as emotional intelligence and goal orientation to lead their tourism firms through economic uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…In the extant literature, many attempts have been made to search for novel strategies that help T&H firms overcome such harsh and turbulent situations. Various recent studies have also pointed to the role of leader in supporting T&H firms to achieve better outcomes during COVID-19 pandemic (Nazarian et al, 2022;Ho et al, 2022;Hahang et al, 2022). For example, Talu and Nazarov (2020) found that leaders relied on their competences such as emotional intelligence and goal orientation to lead their tourism firms through economic uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on leadership during this crisis is important not only because it is relatively under-explored, but also because it carries important social implications and organizational costs (Lombardi et al, 2021). Especially considering that the hotel industry is one of the sectors that has been impacted the most severely by the COVID-19 crisis all over the world, the dynamics and leadership requirements of the industry deserve further attention (Hahang et al, 2022). Since the detrimental impact on overall employee performance is obvious, it is necessary to determine whether leadership style will still have a substantial impact on employee performance under stressful COVID-19 conditions (Shanmugam et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The hotel industry faces more uncertainty and customers are more sensitive to service quality and staff responsiveness (Chan et al , 2021), employees are required to respond flexibly to customer needs. The findings show that SL can effectively stimulate employees’ pro-customer motivation, create a service innovation atmosphere, flexibility, divergent thinking and enhance employees’ CSE, which can be beneficial to keeping and improving organizational resiliency (Hahang et al , 2022). Therefore, hospitality companies should attach more importance to the SL style in human resource management practices.…”
Section: Discussionmentioning
confidence: 99%